A1.31 HLA-B27 over-expression in rats alters central and peripheral monocyte populations. (13th February 2015) - Ansalone, C; Milling, C; Goodyear, CS
Abstract : Background and objectives: HLA-B27 expression is associated with spondyloarthropathy (SpA) and transgenic rats expressing human HLA-B27 and b2-microglobulin (B27 rats) display systemic inflammation and bone loss, which resembles human SpA. We have previously shown that these rats lack a dendritic cell population. However, the myeloid compartment has not been fully characterised. Here, we aimed to characterise monocyte and pre-osteoclast subsets in the bone marrow and blood of B27 rats, and examined the potential of different monocyte/pre-osteoclast subsets to generate mature osteoclasts. Materials and methods: 14–16 week old control (B7) and B27 rats were bled and plasma CCL2 levels were measured by ELISA. Monocytes subsets were analysed and quantified in both the bone marrow and blood of B27, B7 and non-transgenic animals, by evaluation of surface markers (CD172a, CD43, and CD11b) and intracellular uptake of fluorescent M-CSF and CCL2 by flow cytometry. Monocyte populations were FACS sorted and cultured in pro-osteoclastogenic medium for 7 days to evaluate osteoclastogenic potential. Cultures were stained with tartrate-resistant acid phosphatase (TRAP) and mature osteoclasts (TRAP + and ≥3 nuclei) were quantified by light microscopy. Results: A previously unidentified CD172a + CD43 lo CD11b - population of monocytes was observed in the bone marrow. These are bona fide monocytes, expressing CD115 and CCR2, as determined by uptake of fluorescent M-CSF and CCL2 respectively. Interestingly, this new monocyte population was significantly increased in B27 rats. Assessment of the osteoclastogenic potential of bone marrow monocyte subsets revealed that CD172a + CD43 lo CD11b -, but not CD172a + CD43 lo CD11b + monocytes, can differentiate into mature osteoclasts. Furthermore, although CD172a + CD43 lo CD11b - have osteoclastogenic potential, optimal osteoclastogenesis was observed only when all CD43 lo (CD172a + CD43 lo CD11b - and CD172a + CD43 lo CD11b + ) were present. No differences in osteoclastogenesis were observed between B27 and controls rats. Finally, evaluation of circulating monocytes demonstrated that all blood monocytes express CD11b and that the CD43 lo CD11b + population was increased in B27 rats. This corresponded with an increase in CCL2 plasma levels in the B27 rats. Conclusions: We have identified a previously unreported CD11b - monocyte population in the bone marrow of rats, which can differentiate into mature osteoclasts. Along with the numbers of total CD43 lo monocytes, this population is significantly increased in the bone marrow and blood of rats over-expressing HLA-B27. The increase in these populations in the B27 rats may contribute to enhanced inflammation and bone loss.